FERTILIZER SECTORS PULLS THE STRINGS AT BOURSE SINCE 2001 TO 2010 (Global Journal of Management and Business Research, 2012)
The purpose of this study is to see how much fertilizer sector is contributing in the economy of Pakistan, here we see some particulars performance i.e. sale, assets, equity, paid up capital, cash dividend, stock dividend etc. we have taken the data from 2001 to 2010 and run regression analysis and generate different results which we will discuss later. if only the government policies, technology improve then the sector could give its total output, which thus contribute to the economy of the Pakistan which will be benefited for all of us.
Keywords: fertilizer; organic and Capital